(untitled) (Proceedings of International Educators Conference, 2023)
This article provides a comprehensive analysis of the role of continuous education, e-environment, internet, information communications, as well as social environment, family, neighborhood and religion in the formation of national cultural space as factors influencing moral consciousness.